Evaluasi Program Pendidikan Menggunakan Model CIPP - Kuswanto; Sutanti Y; Marsini (Advances In Education Journal, 2026)
Program evaluation in education is essential to determine the effectiveness of program implementation in improving educational quality. This study aims to evaluate educational programs using the Context, Input, Process, Product (CIPP) model. The study employed an evaluative method with a descriptive approach involving principals, vice principals for curriculum, teachers, students, and parents as research subjects. Data were collected through interviews, observations, questionnaires, and documentation. The findings indicate that the context aspect aligns with the needs of schools and students, the input aspect shows adequate resource readiness, the process aspect is implemented according to the plan despite several technical constraints, and the product aspect demonstrates improvements in educational quality. Based on the evaluation results, the program is considered feasible to continue with several improvements to enhance its effectiveness.